2018
DOI: 10.1007/s00705-018-3712-2
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of small RNAs originating from mitoviruses infecting the conifer pathogen Fusarium circinatum

Abstract: Deep sequencing of small RNAs has proved effective in the diagnosis of mycovirus infections. In this study, the presence of mycoviruses in ten isolates of the phytopathogenic fungus Fusarium circinatum was investigated by high-throughput sequencing (HTS) of small RNAs. The contigs resulting from de novo assembly of the reads were aligned to viral genome sequences. The presence of each mycovirus detected in the isolates was confirmed by RT-PCR analysis with four previously described primer pairs and seven new p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 44 publications
2
17
1
Order By: Relevance
“…A high rate of transmission was expected, as mitoviruses FcMV1 and FcMV2-2 are associated with the mitochondria that the offspring inherit from the parents [17]. The high transmission rates of mycoviruses are consistent with those reported for asexual spores of other fungal species such as Ustilaginoidea virens [26] and Epichloë festucae [27] whereas for other pathogens variable rates of virus transmission were observed, e.g., Heterobasidion annosum [13] and CHV1 hypovirus infecting Chryphonectria parasitica [28][29][30].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…A high rate of transmission was expected, as mitoviruses FcMV1 and FcMV2-2 are associated with the mitochondria that the offspring inherit from the parents [17]. The high transmission rates of mycoviruses are consistent with those reported for asexual spores of other fungal species such as Ustilaginoidea virens [26] and Epichloë festucae [27] whereas for other pathogens variable rates of virus transmission were observed, e.g., Heterobasidion annosum [13] and CHV1 hypovirus infecting Chryphonectria parasitica [28][29][30].…”
Section: Discussionsupporting
confidence: 75%
“…Another hypothesis could be that mycoviruses are no longer active or pathogen's parasites and remain in the mitochondria as symbionts, producing no effects on the host. However, this seems unlikely since Muñoz-Adalia [17] found evidences of viral replication detected by high-throughput sequencing such as antisense vsRNA reads. In other Fusarium species, the presence of mycoviruses has not been related to any morphological changes, although it was observed that Fusarium graminearum virus 1 (FgV1) causes hypovirulence [39].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Differential sRNA accumulation and processing of AMV and CqMV1 in infected C. quinoa plants. A number of fungal mitoviruses have been discovered through sRNA characterization, suggesting that, at least in fungi, they are subject to RNA interference (RNAi) processing (28,29). In order to characterize the sRNA present in C. quinoa, we decided to compare three libraries of sRNA: (i) CqMV1-free BO25 infected by AMV (SRA accession no.…”
Section: Resultsmentioning
confidence: 99%